Localization in materials with several conducting bands as a method to boost superconductivity - Vyacheslav D. Neverov; Alexander E. Lukyanov; Andrey V. Krasavin; Arkady A. Shanenko; Mihail D. Croitoru; Alexei Vagov (Communications Physics)
Abstract Strong disorder exerts two opposing effects on a superconducting material. On one hand, it leads to localization of electrons and Cooper pairs, resulting in spatial fragmentation of the condensate state. It enhances the local density of single-particle states, increasing the binding energy of Cooper pairs and the critical temperature at which the condensate state appears. On the other hand, it destroys the long-range coherence, suppressing superconductivity and reducing the corresponding critical temperature. This work demonstrates that if such a disordered superconductor is coupled to a clean or weakly disordered conducting material, the long-range coherence is restored via the proximity effect. As a result, the coexistence of the two subsystems combines the advantages of the high critical temperature of the disordered superconductor and the global supercurrent of the clean one. This synergy effect is robust and can occur in superconducting multi-band and heterostructures, whether they are disordered or have artificial superstructures.